A morphometric comparison of the parietal lobe in modern humans and Neanderthals. Issue 142 (May 2020) - Pereira-Pedro, Ana Sofia; Bruner, Emiliano; Gunz, Philipp; Neubauer, Simon
Abstract: The modern human brain and braincase have a characteristic globular shape including parietal and cerebellar bulging. In contrast, Neanderthals, although having similar endocranial volume, displayed more elongated endocrania with flatter parietal and cerebellar regions. Based on endocranial imprints, we compare the parietal lobe morphology of modern humans and Neanderthals, as this brain region is central to several cognitive functions including tool use and visual imaging. In paleoneurology, shape analyses of endocasts are based either on anatomical landmarks that represent endocranial surface features homologous to cortical convolutions (impressions of brain gyri and sulci) or on dense meshes of semilandmarks that capture overall endocranial shape. Previous analyses using the former suggested that modern humans have relatively longer and taller parietal lobes than extinct human species, while the latter emphasized parietal bulging without a significant size difference of parietal regions. In the present study, we combine both anatomical landmarks and surface semilandmarks to investigate the morphological differences of the parietal lobes between modern humans and Neanderthals. Despite limitations by landmark uncertainty, our analyses were able to detect and confirm average different parietal shapes, with modern humans displaying taller and anteroposteriorly extended parietal lobes. We also show mean size differences, with modern humans displaying slightly larger surface areas on the dorsal posterior parietal region, and on a lateral region comprising the supramarginal gyrus, angular gyrus, and intraparietal sulcus. While we observed average differences in the parietal form between the two species, their ranges of distribution overlap, indicating the differences could be a matter of degree. Thus, further analyses on intraspecific variation in parietal lobe morphology within modern human brains should help understand the differences between globular and elongated endocrania. This is crucial because changes to the parietal cortex might affect associative and integrative functions between somatic and visual primary inputs.